Impact of Immersive Technology Applied in Computer Graphics Learning - Moreira, Paulo Muggler; de Oliveira, Elen Collaço; Tori, Romero (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2016)
In this paper we describe an application of immersive technology to a specific learning context. In this case, a Virtual Reality environment was created for the purpose of delivering lesson content in a Computer Graphics module for students of engineering and architecture courses. The virtual environment was designed to demonstrate lighting model algorithms and aspects of 3D rendering techniques. An experiment was carried out in which students were divided into two groups that viewed the same lesson content: experimental and control group. In this pilot study we describe the application in details and discuss preliminary results based on analysis of the participants perceptions collected through presence questionnaire. Our results revealed that the experimental group showed higher levels of presence and involvement compared with the control group.